Solidaritas Sosial pada Tradisi Panjang Mulud Nabi di Desa Sukarame Kecamatan Cikeusal Kabupaten Serang Banten - Suntiyah, Suntiyah; Kudus, Wahid Abdul; Soetrisnaadjisandjaja, Denny (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The implementation of the long tradition of mulud in Sukarame Village found several unique features. These include processions showing the luxury of long mules as well as creating road congestion, thereby disrupting public traffic. There is an obligation to pay a joint contribution of around Rp. 500,000, but the economic capacity of each resident of Sukarame Village is different; however, people who are less well off are relieved to contribute half of what has been determined because the people of Sukarame Village have a sense of concern for others and uphold a high sense of social solidarity. Even though they are free to pay half, it also creates a sense of social jealousy for other parts of society. This research uses a qualitative paradigm using ethnographic methods. The research aims to describe the phenomenon that occurs regarding social solidarity in the long tradition of mulud. The data collection techniques use field observation, interviews, and documentation. Meanwhile, data analysis uses data collection techniques, data reduction, data presentation, drawing conclusions, or verification. The results of the research found that social solidarity was built on the long tradition of the Prophet's mulud, namely: the procession activities were quite well established, making relationships closer, making the sense of solidarity stronger because a sense of kinship had been formed by itself, making them prioritize each other's public interests rather than personal interests. The existence of mutual cooperation activities includes making long houses in the form of houses. The creativity that is possessed makes community relations closer, making solidarity stronger, and by doing mutual cooperation, creating a sense of mutual help. The existence of deliberation activities, including the placement of days and the formation of committees with the involvement of various parties, can foster a sense of unity and a sense of shared destiny. With the ngariung activity, there is a shared belief in gaining blessings, safety, and maintaining the beliefs that are held.